Perturbed best response dynamics in a hawk-dove game - Volker Benndorf; Ismael Martinez-Martinez (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
We examine the impact of behavioral noise on equilibrium selection in a hawk-dove game with a model that linearly interpolates between the one- and two-population structures in an evolutionary context. Perturbed best response dynamics generates two hypotheses in addition to the bifurcation predicted by standard replicator dynamics. First, when replicator dynamics suggests mixing behavior (close to the one-population model), there will be a bias against hawkish play. Second, polarizing behavior as predicted by replicator dynamics in the vicinity of the two-population model will be less extreme in the presence of behavioral noise. We find both e.ects in our data set.
Keywords: C62; C73; C91; C92; 330; evolutionary game theory; perturbed best response dynamics; experiment in continuous time; hawk-dove game